Bacteriological Profile and Antibiogram of Neonatal Septicemia - Bhatt , Sima K; Patel , Disha A; Gupta , Praveg; Patel , Kiran; Joshi , Gurudutt (National Journal of Community Medicine, 2012)
Background: Early diagnosis and proper management of neonatal septicemia can bring down the morbidity and mortality substantially.4 Hence the aim of this study was to study the bacteriological profile of neonatal septicemia cases and their antibiogram for planning strategy for the management of these cases. Methodology: A retrospective study of bacterial isolates from cases of neonatal septicemia was undertaken over a period of 13 months from January 2006 to February 2007 at B.J.Medical College, Civil Hospital, Ahmedabad, Gujarat. Result: Blood culture was positive in 55.6% of cases. Gram negative septicemia was encountered in 63% and it was predominant septicemia compared to gram positive septicemia. Klebsiella species (59.10%) and Escherichia coli (31.99%) were the predominant pathogens followed by Pseudomonas, Acinetobacter and Citrobacter species. The most effective antimicrobials against Klebsiella species and Escherichia coli were Carbapenems followed by Piperacillin + Tazobactam, 2nd generation Quinolones and Amoxicillin + Clavulonic acid. Where as in case of Pseudomonas 2nd generation Quinolones were most effective followed by Carbapenems, Aminoglycosides, Piperacillin + Tazobactam, Ceftazidime and Aztreonam. Out of 187 gram positive isolates, 171 (91.4%) were coagulase negative staphylococci, 8 (4.3%) were staphylococcus aureus, and 8 (4.3%) were streptococci. Gram positive isolates were more sensitive to Vancomycin followed by Linezolid, Clindamycin and higher Quinolones. Conclusion: Neonatal septicemia is a life-threatening emergency, and rapid treatment with antibiotics is essential for favourable outcome. For effective management of neonatal septicemia cases, strategy of antibiotic usage in the hospital must be reviewed.